2018
DOI: 10.1111/jsap.12814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and disease associations in feline thrombocytopenia: a retrospective study of 194 cases

Abstract: Thrombocytopenia in cats may be more prevalent than previously reported and severe thrombocytopenia may be associated with spontaneous haemorrhage. Severe thrombocytopenia in cats appears less commonly immune-mediated than in dogs. Thrombocytopenia did not appear to be associated with retroviral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Clinical signs depend on viral subgroup and the stage of disease. Common general clinical signs include anemia (pale gums), hyporexia, decreased stamina, depression, diarrhea or constipation, excessive drinking and urination, infertility, jaundice, fever, lymphadenopathy, weight loss, poor coat condition, and neuropathies, with subsequent anisocoria, and hind limb paralysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs depend on viral subgroup and the stage of disease. Common general clinical signs include anemia (pale gums), hyporexia, decreased stamina, depression, diarrhea or constipation, excessive drinking and urination, infertility, jaundice, fever, lymphadenopathy, weight loss, poor coat condition, and neuropathies, with subsequent anisocoria, and hind limb paralysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…PLT aggregation in feline blood samples is common, with reported prevalence ranging between 40% and 70% ( 21 , 57 60 ). In this study, PLT aggregation occurred in 27% of the WB samples and in 7% of the PRP samples, with no evidence of PLT aggregation in the PPP samples.…”
Section: Discussionmentioning
confidence: 99%
“…Three cats with cardiac diseases also presented hemostatic disorders, including aortic or pulmonary thromboembolism, hemothorax, and disseminated intravascular coagulation [42]. A recent retrospective study performed at a UK hospital aiming to assess the prevalence of thrombocytopenia in 194 cats showed in subjects with cardiovascular disease a prevalence of 5% vs. 4% of cats with normal platelet count (P not significant) [43]. Conversely, a study on thrombocytosis observed this finding in 5 out of 51 cases of cardiovascular diseases: HCM, ATE, hypertension and thromboembolic disease.…”
Section: Coagulative Profilementioning
confidence: 99%